Prevalence of Stunted Infants and Toddlers in Sub-Urban Areas and Watersheds of Pekanbaru City - Hamida Sari Batubara; Zahtamal; Ridha Restila; Aisyah Ratu Ikhsan; Tia Masita Rosadi; Resti Palupi (PT Inovasi Pratama Internasional, 2023)
Stunting refers to a child who is too short for his age. Based on Pekanbaru City Health Office's data, geographically Siak watershed and sub-urban areas have higher stunting cases than other areas. This study using a descriptive epidemiological study from using e-PPGBM report 2021. The results obtained were monitoring the nutritional status of children under five at the Posyandu in the area studied with complete data ( Puskesmas Lima Puluh and Rumbai Bukit) are 54.8% and 12.56% respectively. The average age of stunted children in the study locations (Puskesmas Limapuluh , Rejosari and Rumbai Bukit) were 37, 38, and 29 months. Based on gender, the majority of stunted children are females. Judging from the indicators for TB/U and BB/U, most of the stunted children are in the short category and are undernourished. However, from the ratio of BB/TB, most of the stunted children have normal nutrition category.